2020
DOI: 10.1073/pnas.1914853117
|View full text |Cite
|
Sign up to set email alerts
|

Loss of insulin signaling may contribute to atrial fibrillation and atrial electrical remodeling in type 1 diabetes

Abstract: Atrial fibrillation (AF) is prevalent in diabetes mellitus (DM); however, the basis for this is unknown. This study investigated AF susceptibility and atrial electrophysiology in type 1 diabetic Akita mice using in vivo intracardiac electrophysiology, high-resolution optical mapping in atrial preparations, and patch clamping in isolated atrial myocytes. qPCR and western blotting were used to assess ion channel expression. Akita mice were highly susceptible to AF in association with increased P-wave duration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 65 publications
(83 reference statements)
1
29
1
Order By: Relevance
“…32,33 Recently, it has been shown that Akita and STZ models of T1DM are characterized by substantial increases in AF susceptibility and duration in association with electrical remodeling of the atria. 34,35 P-wave durations were prolonged in both models, and atrial conduction velocity was reduced in Akita mice. Detailed electrophysiological and molecular studies demonstrated that atrial AP upstroke velocity (V max ) was reduced, and APD was prolonged in Akita mice.…”
Section: Atrial Remodeling and Af In T1dmmentioning
confidence: 93%
See 2 more Smart Citations
“…32,33 Recently, it has been shown that Akita and STZ models of T1DM are characterized by substantial increases in AF susceptibility and duration in association with electrical remodeling of the atria. 34,35 P-wave durations were prolonged in both models, and atrial conduction velocity was reduced in Akita mice. Detailed electrophysiological and molecular studies demonstrated that atrial AP upstroke velocity (V max ) was reduced, and APD was prolonged in Akita mice.…”
Section: Atrial Remodeling and Af In T1dmmentioning
confidence: 93%
“…39 In contrast, Akita atrial myocytes showed no changes in mRNA expression of Cx40. 34 Cx43 is also expressed in the atria but was unchanged in the atria in Akita mice. 34 More research is needed in this area to understand the role connexins play in T1DM.…”
Section: Atrial Remodeling and Af In T1dmmentioning
confidence: 95%
See 1 more Smart Citation
“…By contrast, our analysis had sufficient statistical power to demonstrate that (1) type 1 diabetes was also associated with a significantly higher incidence of AF than in non-diabetics patients, indicating that insulin resistance would not be the only promoter of AF in patients with diabetes (2) this association was seen both in men and in women, (3) the adjusted hazard ratios for the risk of AF were actually even higher than for type 2 diabetes, particularly for women and (4) the higher relative risk of AF in women was seen across all ages, the women-to-men ratio being around 1.8 at age 45 and progressively decreasing with increasing age, which was somewhat different than what was seen for type 2. Recent pre-clinical studies suggested that loss of insulin signalling may contribute to atrial electrical remodelling and atrial fibrillation in murine models of type 1 diabetes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One group showed that decreased phosphoinositide 3-kinase (PI3K) activity, which is downstream of the insulin receptor, contributes to increased action potential duration in both type 1 and type 2 diabetics’ cardiomyocytes, and this was mediated by increased late sodium current [ 113 ]. Another group has shown that type 1 diabetic atrial myocytes have decreased sodium flux, which is corrected by insulin treatment [ 114 ]. Although the pathophysiology of type 1 diabetes is different in several important ways from type 2 diabetes, which is much more common in obese adults, the results may have some relevance to DIO and HFD arrhythmogenesis.…”
Section: Additional Metabolic Mechanisms That Potentially Regulatmentioning
confidence: 99%